Pengaruh Kualitas Pelayanan Terhadap Kepuasan Masyarakat Pencari Keadilan Pada Pelayanan Terpadu Satu Pintu - Indah Mawarni; Irsan; Roy Saleh; Nanda Revita; Marita Pratisila (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2022)
This study aims to determine the Effect of Service Quality on Community Satisfaction at the Kayuagung District Court. The sample in this study was the people who were present at the Kayuagung District Court as many as 103 respondents. This study took samples using the Proportionate Stratified Random Sampling technique. The analysis method used is a quantitative descriptive analysis method using statistical formulas adapted to the research to assess the results of filling out questionnaires and tested through statistical testing. The test results of the instruments in variable X (Quality of Service) and variable Y (Community Satisfaction) using the validity test are valid with a calculated value of 0.492 and the results of the reability test are with a value of rCalculate = 1.0823 >0.60. These results mean that the research instruments used are declared realiable. Meanwhile, the results of the linear regression test on the hypothesis, showed that the variable X had a positive effect on the variable Y by 0.961%, the test value of the coefficient of determination was 24.2% and the result of the T Test obtained also a significant effect with the value of tcount = 5.680 greater than the value of t table, which means that Ho rejected and Ha accepted or in other words there is a positive and significant relationship between the Quality of Service to Community Satisfaction in the Kayuagung District Court. However, based on the results of the questionnaire that was distributed, there were several statements that received disagreements / strongly disagreed regarding empathy from service personnel, facilities and infrastructure and others. The advice from the author after conducting research at the Kayuagung District Court is to make improvements regarding facilities and infrastructure as well as improve the quality of officer services by providing training related to service and ethics.